Khutbah Jum’at Di Kota Samarinda (Analisis Kesiapan Para Khotib Di Kota Samarinda) - M. Tahir (FENOMENA, 2013)
Friday Khutbah is one of the Friday prayers at the same time as a form of da’wah. Khotib as a da’i and the congregation of Friday prayers as a proselytizing receiver. One thing that is undeniable in the implementation of the Khutbah is the tendency of the mosque congregation to move where the choosing of Khotib who able to give new nuances in his speech, although, he has to travel relatively far to find a sympathetic Khotib. Khutbah will be interesting if delivered with feeling and the involvement of Khotib with the issues discussed . To achieve high quality Khutbah, a Khotib needs a long process. He must constantly improve their knowledge, develop skills and expand his experience with continuous training. In addition, the power of creativity and style of well-groomed appearance will also contribute to determine the success of Khutbah.